Teacher performance appraisal in Pre-school, Primary and Secondary Education in Portugal: a brief historical perspective (Revista Internacional de Formação de Professores, 2022)
The teacher performance appraisal is a matter that generates interest among educational agents, students and society in general, as it is one of the most important aspects to guarantee and improve the quality of education. However, it is a complex and controversial process, which in Portugal has been defined through an intense legislative activity, especially since 1990. In this paper, a brief historical perspective is presented in order to understand the bases of the current model of performance appraisal of pre-school, primary and secondary teachers.
Keywords: Teacher performance appraisal; Pre-school primary and secondary teachers; Portugal; Educational policy